Prevalence and correlates of postabortion long-acting reversible contraceptive (LARC) use among young women (24 and below) in Nepal: Strategy in the search for improvements - Suresh Mehata; Navaraj Bhattarai; Jamie Menzel; Mukta Shah; Pratik Khanal; Shadie Tofigh; Mukti Nath Khanal; Shibesh Chandra Regmi; Kathryn Andersen (BMC, 2019)
Abstract Introduction Postabortion contraceptive use differs across countries, suggesting the need for country-level research to identify barriers and suggest appropriate interventions. This study aimed to identify the prevalence and correlates of postabortion long-acting reversible contraceptive (LARC) use among women aged 24 or younger in Nepal. Methods This is a cohort study using Health Management Information System (HMIS) data where individual case records of women seeking induced abortion or postabortion care were documented using structured HMIS 3.7 records. Analysis was performed on the individual case records of 20,307 women 24 years or younger who received induced abortion or postabortion care services in the three-year period from July 2014 to June 2017 at 433 public and private health facilities. Findings Overall, LARC uptake during the study period was 11% (IUD: 3% and implant: 8%). The odds of LARC acceptance was higher for young women (24 and below) who belonged to Brahmin/Chhetri (AOR = 1.23; 95% CI: 1.02-1.47) and Janajatis (AOR = 1.20; 95% CI: 1.01-1.43) as compared to Dalits; young women who had an induced abortion (AOR = 3.75; 95% CI: 1.75-8.06) compared with postabortion care; and those receiving service from public sector health facilities (AOR = 4.00; 95% CI: 2.06-7.75) compared with private sector health facilities. Conclusion The findings from this study indicate the need to focus on barriers to acceptance of LARC among several groups of young women (24 and below) receiving abortion care in Nepal: Dalits, Madhesis and Muslims; nulliparous women; and those receiving services at private sector health facilities.